Hubungan Family Centered Care dengan Tingkat Kecemasan Anak Usia Prasekolah - Dominggus Kendu; Ika Arum Dewi Satiti; Risqiana Dita Ekasari (Media Husada Journal Of Nursing Science, 2026)
Family Centered Care (FCC) is a care approach that places families as partners in the child care process. Preschool children often experience anxiety when they are in unfamiliar environments or undergoing care, making family involvement essential. This study aimed to determine the relationship between Family Centered Care and anxiety levels in preschool-aged children. This research used a correlational analytic design with a cross-sectional approach. The sample consisted of 31 preschool children selected through total sampling. Data were collected using validated and reliable Family Centered Care and child anxiety questionnaires. Data analysis used the Spearman Rank test with a significance level of p<0.05. The results showed a significant relationship between Family Centered Care and anxiety levels in preschool children (p=0.001; r=-0.65). These findings indicate that better implementation of FCC is associated with lower anxiety levels in children. This study emphasizes the importance of active family involvement in the care of preschool-aged children to reduce anxiety and improve their comfort. Keywords: Family Care, Anxiety, Preschool Children